2021
DOI: 10.1021/acs.energyfuels.1c02610
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of Core–Shell Heterostructure CePO4@CuCo2S4 As Advanced Electrodes for High-Performance Supercapacitor

Abstract: The design of multicomponent core–shell heterostructures is considered to be an efficacious way to develop excellent performance supercapacitor electrode materials. A new strategy CePO4@CuCo2S4 core–shell heterogeneous structure is devised by preparing porous CePO4 nanosheets as cores via hydrothermal reaction and solid-state phosphating methods and electrochemically deposited CuCo2S4 nanosheets as shells. Binder-free three-dimensional (3D) porous CePO4@CuCo2S4 nanosheets grown on foam nickel substrate can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Especially, NCS/CNT shows an excellent capacity of 603 C g –1 . CePO 4 @CuCo 2 S 4 exhibits an outstanding capacitance (2897.8 F g –1 at 0.5 A g –1 ) . CuO/CF@NiCoMn-OH exhibits a high capacitance of 26.8 F cm –2 at 8 mA cm –2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, NCS/CNT shows an excellent capacity of 603 C g –1 . CePO 4 @CuCo 2 S 4 exhibits an outstanding capacitance (2897.8 F g –1 at 0.5 A g –1 ) . CuO/CF@NiCoMn-OH exhibits a high capacitance of 26.8 F cm –2 at 8 mA cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…35 CePO 4 @CuCo 2 S 4 exhibits an outstanding capacitance (2897.8 F g −1 at 0.5 A g −1 ). 36 CuO/CF@NiCoMn-OH exhibits a high capacitance of 26.8 F cm −2 at 8 mA cm −2 . 37 NiMoO 4 /V 2 CTx@rGO shows a capacitance of 1022 F g −1 at 1 A g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…31,32 To further realize their commercial application, introducing transition metal sulfides with high electrical conductivity to enhance the electrochemical properties of CoMoO 4 and MoO 3 may be a promising strategy. Transition metal sulfides are regarded as auspicious electrode materials for supercapacitors, 33 which possess outstanding electrochemical behavior, such as excellent conductivity, low electronegativity, better cycling stability, higher energy density and ionic diffusivity. 34,35 Additionally, some reports indicated that the electrochemical performance of multi-component transition metal sulfides is better than that of individual sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the construction of composite structures is well-known as an effective modification approach for boosting photocatalytic performance. CuCo 2 S 4 is a typical thiospinel compound that is used in many fields such as the preparation of solar cells, 7 construction of supercapacitors, 8 and production of lithium-ion batteries. 9 Several properties of CuCo 2 S 4 including the electronic band structure, thermal stability, and controllable morphology make it a unique photocatalyst.…”
Section: Introductionmentioning
confidence: 99%